A new species of Murina (Chiroptera: Vespertilionidae) from sub-Himalayan forests of northern Myanmar - Soisook, Pipat; Thaw, Win Naing; Kyaw, Myint; Lin Oo, Sai Sein; Pimsai, Awatsaya; Suarez-Rubio, Marcela; Renner, Swen C. (Zootaxa, 2017)
A new species of Murina of the suilla-type is described from the Hkakabo Razi Landscape, Kachin, Upper Myanmar, an area that is currently being nominated as a World Heritage Site. The new species is a small vespertilionid, with a forearm length of 29.6 mm, and is very similar to M. kontumensis, which was recently described from Vietnam. However, it is distinguishable by a combination of external and craniodental morphology and genetics. The DNA Barcode reveals that the new species clusters sisterly to M. kontumensis but with a genetic distance of 11.5%. A single known specimen of the new species was collected from a lowland forest area in the plains of the Hkakabo Razi landscape, south-eastern Himalaya. Additional information on ecology, echolocation, and conservation are included. The high cryptic diversity of the genus Murina in Southeast Asia, as well as the Hkakabo Razi Landscape being a bat diversity hotspot, is highlighted.